Optimalisasi Penguatan Agama Melalui Regenerasi Dan Kader Di Desa Tewang Kadamba - Pransinartha Pransinartha; Ervantia Restulita L. Sigai; Gito Supriadi; Dicky Wahyudi; Fikri Shaumazzaki Siddiq; Eka Nalaratih; Niluh Puspita Sari; Andani Nainggolan; Kristina Ida Wati Pasaribu; Multi Sentosa Nusan; Tiara Theresa; Ketut Artiani; Eka Nurmawati; Gusvi Ainur Ridho Isnor (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Tewang Kadamba Village is a village located in Katingan Regency, Central Kalimantan Province. In this village, there are various ethnic groups and the dominant language is the Dayak Kaharingan and there are also three religions namely Hinduism, Islam and Christianity where the dominant religion is Islam and Hindu Kaharingan. Seen from a religious perspective, even though there are differences they still maintain, appreciate, respect, and tolerate these differences. There is one problem or problem regarding religious knowledge and enthusiasm for worship in Tewang Kadamba Village. In this regard, the purpose of this study is to find out and describe religious understanding and how people acquire religious knowledge and strengthen religion through regeneration and cadres. The method used is PAR. The results of community service are good understanding of religion and ways to acquire religious knowledge through school education and activities in places of worship. Then related to strengthening religion through regeneration and cadres is a good idea for empowering the people of Tewang Kadamba Village.